(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
In the work are presented volumetric properties of dimethylsulfoxide (DMSO) and diethylsulfoxide (DESO). Densities of binary mixtures of DMSO–water and DESO–water have been measured at temperatures from 298,15 to 343.15 K by means of a vibrating-tube densimeter (DMA 4500), as well as thermal denaturation DNA and human serum albumin of the above mentioned systems. Having certain beliefs about structural particularity of the system sulfoxide–water, became possible to present and explain the process of melting DNA and protein. We have come to the conclusion that DMSO and DESO, in defined concentration rang, stabilize the double spiral DNA and are denaturizing agents for protein.